Pengaruh Promosi dan Saluran Distribusi terhadap Kepuasan Pelanggan - Nasruddin Nasruddin; Nurchayati Nurchayati (IPM2KPE, 2019)
This study aims to determine the effect of promotion and distribution channels on customer satisfaction on the CV. Sinar Laut Baru Lubuklinggau. This study uses multiple regression, to find out how far the influence of independent variables on the dependent variable. The results of the study, the results of the t test calculation can be concluded that the Promotion (X1) has an effect on customer satisfaction (Y), showing the value of t = 4.503 is greater than the value of the table (2.036). The results of t test calculations that the distribution channel (X2) affect the Customer Satisfaction (Y), show the value of t = 4.312 is greater than the value of the table (2.036). 3). The recapitulation of the Fcount test results obtained was 14.255> Ftable = 3.29. Conclusions, jointly (simultaneously) promotion and Distribution Channels have a significant effect on Customer Satisfaction Keywords: Promotion, Distribution Channels, Customer Satisfaction